Relationship between Mast Cell Density and Microvessel Density in Oral Squamous Cell Carcinoma and Normal Oral Mucosa: Immunohistochemical Analysis using CD117 and CD34 Antibodies - Ansari, Fakeha (International Journal of Pathology, 2023)
Introduction: Mast cells are reported to be linked with the promotion of tumorigenesis in several malignancies. Present study was aimed at determining any potential relationship between mast cells and angiogenesis in different grades of oral squamous cell carcinoma (OSCC) and comparing them to normal oral mucosa (NOM). Methodology: In this analytical comparative cross sectional study, 40 tissue sections were examined, 20 cases were diagnosed as OSCC and other 20 as NOM. To measure mast cell density (MCD) and microvessel density (MVD), immunohistochemical analysis comprised reacting formalin-fixed, paraffin-embedded blocks with monoclonal CD117 and CD34 antibodies respectively was performed . Statistical analysis included a t-test, ANOVA, and Pearson correlation, and a p-value of < 0.05 and a 95% confidence interval were considered significant. Results: In OSCC, the mean (SD) MCD and MVD were 22.4 (10.8) and 22.3 (7.48), respectively. MCD and MVD were shown to have a strong negative correlation (r = -.702, p- value =.001). In the grade 3 OSCC, the MCD was lower than the mean MCD found in NOM. MVD was found to have a positive correlation with tumor progression (r =.895, p-value =.001). The mean (SD) MCD and MVD in OSCC and NOM were 22.4 (10.8) and 11.5 (2.58), respectively, and no significant relationship between MCD and MVD was identified. Conclusion: In OSCC, a negative correlation between MCD and MVD is reported. When compared to NOM .MCD is found to be significantly higher in OSSC in the initial stages, but it subsequently declines in later stages, raising the possibility of protective effect by immune regulation.